Carbon-carbon bond formation reactions. Part I : classical aldol reaction. Part II : contemporary C-H bond activation/functionalization - Chok, Yew Keong (2015)
Since the serendipitous synthesis of urea by Frederich Wöhler in 1828, which marked the birth of organic synthesis, this craft had been perfected by synthetic chemistry to such an extent where not only can such biomacromolecules as proteins and genes be manipulated and assembled in vitro at will, but also natural products of seemingly boundless complexity and intrigue can be synthesized in the laboratory following logical approaches from readily available starting materials.